Mother Tongue Education for Tribal Children - Gandhi, Malli (JOURNAL OF INDIAN EDUCATION, 2014)
This paper attempts to discuss the status, problems and issues relating to tribal children and their languages through an exploration of policies, curricular frameworks and practices at state and national level. The paper also tries to explore the intricate relationship between tribal languages, culture, society and literature in the development of STs in a pluralistic society like India. However, the paper mainly focuses on the importance of mother tongue education in tribal schools, the position of the tribal languages in India, innovations in the development of tribal languages and education, identifying current problems and issues and to suggest suitable measures in helping tribal children to bridge the gap between the home language of the tribal children and the state language by sustaining mother tongue in tribal schools. The paper suggests the need to shift from the stage of advocacy to the stage of empowerment in dealing with the issues of tribal communities.